THE LARGEST ASIATIC AMPHECHINUS (ERINACEIDAE, INSECTIVORA, MAMMALIA) FROM THE OLIGOCENE OF MONGOLIA - Lopatin A.V. (My University, 2002)
A lower jaw fragment of a new hedgehog species, Amphechinus gigas sp. nov., from the Oligocene Shand-Gol Formation of Mongolia is described. This species is substantially larger than A. rectus, A. akespensis and other known Amphechinus species from Asia and comparable in size to the European species A. robustus, A. ginsburgi, and A. intermedius. Regarding the length of the lower cheek tooth row, A. gigas is comparable to Recent Erinaceus europaeus; however, the much deeper and more massive horizontal ramus of the dentary shows that A. gigas is larger than the latter.
Keywords: Oligocene; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен